Release of virus-like particles from cells infected with poliovirus replicons which express human immunodeficiency virus type 1 Gag. - Porter, D C (1996)
The effectiveness of attenuated poliovirus vaccines when given orally to induce both systemic and mucosal immune responses against poliovirus has resulted in an effort to develop poliovirus-based vectors to express foreign proteins. We have previously described the construction of poliovirus genomes (referred to as replicons) in which the complete human immunodeficiency virus type 1 (HIV-1) gag gene was substituted for the capsid gene (P1) (D.C. Porter, D.C. Ansardi, and C.D. Morrow, J. Virol. 69:1548-1555, 1995). Infection of cells with encapsidated replicons resulted in the expression of a 55-kDa protein. To further characterize the biological features of the HIV-1 Gag proteins expressed in cells infected with encapsidated replicons, we utilized biochemical analysis and electron microscopy. Expression of the 55-kDa protein in cells infected with encapsidated replicons resulted in myristylation of the Pr55gag protein. The Gag precursor protein was released from infected cells; analysis on sucrose density gradients revealed that the precursor sedimented at a density consistent with that of an HIV-1 virus-like particle. Analysis of replicon-infected cells by electron microscopy demonstrated the presence of condensed structures at the plasma membrane and the release of virus-like particles. These studies demonstrate that poliovirus-based vectors can be used to express foreign proteins which require posttranslational modifications, such as myristylation, and assemble into higher-order structures, providing a foundation for the future use of poliovirus replicons as vaccine vectors.